2008
DOI: 10.1111/j.1542-474x.2008.00219.x
|View full text |Cite
|
Sign up to set email alerts
|

Baroreflex Sensitivity: Measurement and Clinical Implications

Abstract: Alterations of the baroreceptor-heart rate reflex (baroreflex sensitivity, BRS) contribute to the reciprocal reduction of parasympathetic activity and increase of sympathetic activity that accompany the development and progression of cardiovascular diseases. Therefore, the measurement of the baroreflex is a source of valuable information in the clinical management of cardiac disease patients, particularly in risk stratification. This article briefly recalls the pathophysiological background of baroreflex contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
433
0
9

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 519 publications
(453 citation statements)
references
References 81 publications
11
433
0
9
Order By: Relevance
“…Clinical evidence has associated arterial baroreflex dysfunction with many cardiovascular diseases, the sudden death of patients suffering acute myocardial infarction and mortality in patients with congestive heart failure. 17 Changes in neural-cardiovascular integration due to NO deficiency may be the main cause of autonomic abnormalities in several models of experimental hypertension 2 as a consequence of impaired arterial baroreflex. 3,18 As a result of augmented ASS activity, an enzyme also expressed in the CNS, 6 and central effects on the control of blood pressure 11,14 in the presence of Bj-PRO-10c, we expected to observe increased NO production in the brain and improved arterial baroreflex function in conscious SHRs.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical evidence has associated arterial baroreflex dysfunction with many cardiovascular diseases, the sudden death of patients suffering acute myocardial infarction and mortality in patients with congestive heart failure. 17 Changes in neural-cardiovascular integration due to NO deficiency may be the main cause of autonomic abnormalities in several models of experimental hypertension 2 as a consequence of impaired arterial baroreflex. 3,18 As a result of augmented ASS activity, an enzyme also expressed in the CNS, 6 and central effects on the control of blood pressure 11,14 in the presence of Bj-PRO-10c, we expected to observe increased NO production in the brain and improved arterial baroreflex function in conscious SHRs.…”
Section: Introductionmentioning
confidence: 99%
“…HR was derived from the AP wave. The evoked BRS was measured by the Oxford method in which randomized, intravenous boluses of graded doses of phenylephrine or sodium nitroprusside (2, 5, and 10 g/kg in 0.9% NaCl) are given to increase or decrease pressure, respectively (26). The BRS was determined for each animal as the slope of the relationship between changes in MAP and the pulse interval (60,000/HR).…”
Section: Animalsmentioning
confidence: 99%
“…Recently Wichi et al (2005) found that maternal diabetes impairs baroreflex control of heart rate (HR) in offspring of STZ-induced diabetic mothers. Because attenuation of baroreflex sensitivity is associated with many cardiovascular diseases including sudden death (La Rovere et al 2008), it is critically important to study the effects of maternal diabetes on the neural components within the baroreflex circuitry.…”
Section: Introductionmentioning
confidence: 99%